TiO₂/Chitosan-Moringa oleifera Nanocomposites for Wound Dressings: A Systematic Review - Misriyani; Damayanti, Nita; Halim, Wijoyo (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2026)
Chronic wounds present a major clinical challenge due to persistent infection, oxidative stress, and inflammation that delay healing. TiO₂/chitosan nanocomposites enriched with Moringa oleifera extract have shown potential to enhance wound healing through antibacterial, antioxidant, and anti-inflammatory activities. This systematic review aimed to synthesize current evidence on the development, properties, and biological mechanisms of these composites. A literature search was conducted in PubMed, Embase, and Web of Science up to September 2025 following PRISMA 2020 guidelines. Eligible studies included experimental, preclinical, and clinical research. Data extraction and quality assessment were performed independently. Thirteen studies met the inclusion criteria. The findings indicate that TiO₂ nanoparticles improve mechanical strength and antibacterial activity, while chitosan contributes biocompatibility and intrinsic antimicrobial effects. Moringa oleifera extract provides bioactive compounds that enhance antioxidant activity and modulate inflammation. These composites promote wound closure and tissue regeneration. However, most studies remain preclinical with methodological heterogeneity. Further standardized in vivo studies and clinical trials are required to confirm their long-term safety and therapeutic effectiveness.